Central bank independence and inflation in Africa: The role of financial systems and institutional quality - Abel Mawuko Agoba; Joshua Abor; Kofi A. Osei; Jarjisu Sa-Aadu (Central Bank Review (CBR), 2017)
The study examines the effects of financial systems and the quality of political institutions on the effectiveness of central bank independence in achieving lower inflation. Drawing from the fiscal theory of price level (FTPL) and political economy of macroeconomic policy (PEMP) literature; we estimate a panel regression model, using Two Stage Least Squares instrumental variables procedure, on a sample of 48 African countries over the period 1970-2012. The study finds that central bank independence-inflation nexus is dependent on the model, sample and estimation technique used. After accounting for various control variables and introducing inflation targeting as an additional explanatory variable, the study shows that, unlike in developed countries, CBI is not sufficient in achieving lower inflation in Africa and the developing world. However, common to developed, developing and African countries, is that, higher central bank independence is more effective in lowering inflation in the presence of high levels of banking sector development and institutional quality. The findings of the study also show that while stock market development enhances the effectiveness of CBI in developed and developing countries, it has no significant effect on CBI effectiveness in Africa.
Keywords: 330; Central bank independence; Inflation; Africa; Financial development; Institutional quality